An investigation of the effect of psychological capital on the burnout of nurses in a military hospital in Tehran - A nezami; H Givarian (فصلنامه ابن سینا)
Background: Psychological capital is a new subject that emphasizes on capabilities and assets of an individual. It also considers the positive aspects of human life and tries to facilitate presence of these positive elements in human life from a scientific and practical view. Given the increasing approach to the psychological capital in organizations, the present article aimed to investigate the effect of psychological capital on burnout of nurses in a military hospital in Tehran.